Analisis Aliran Air Tanah Menggunakan Groundwater Velocimeter Pada Lahan Gambut Tropis - Gustin, Silvie Welya; Sutikno, Sigit; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydrologic restoration using canal block is a developing way for re-wetting peatlands, like as in Lukun Village, Tebing Tinggi Timur, Meranti Islands. The groundwater flow around the canal block should be analyzed to determine the effect of the canal block on the surrounding peatland. The analysis was carried out using Groundwater Velocimeter tool in pairs around the canal block. The results obtained from Grounwater Velocimeter is velocity and direction of groundwater flow shown from of ink on the paper. The direction of groundwater flow on peatlands are irregular as it depends on the elevation and pressure difference in area. Keywords : Groundwater Velocimeter, Groundwater Flow, Peatland